2013
DOI: 10.1007/s00122-013-2246-y
|View full text |Cite
|
Sign up to set email alerts
|

Fine genetic characterization of elite maize germplasm using high-throughput SNP genotyping

Abstract: To investigate the genetic structure of Chinese maize germplasm, the MaizeSNP50 BeadChip with 56,110 single nucleotide polymorphisms (SNPs) was used to genotype a collection of 367 inbred lines widely used in maize breeding of China. A total of 41,819 informative SNPs with minor allele number of more than 0.05 were used to estimate the genetic diversity, relatedness, and linkage disequilibrium (LD) decay. Totally 1,015 SNPs evenly distributed in the genome were selected randomly to evaluate the population stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(120 citation statements)
references
References 32 publications
12
101
6
1
Order By: Relevance
“…These values are very close to those determined by Wu et al (2014) using 41,819 SNPs across 367 inbred lines and finding values of 0.364 and 0.291, respectively. However, the values for average gene diversity and PIC in the present study are much smaller than those obtained in the three previous studies (Xie et al 2007;Yang et al 2010;Yu et al 2007), all of which found average gene diversity and PIC values of[0.500.…”
Section: Genetic Diversitysupporting
confidence: 79%
See 4 more Smart Citations
“…These values are very close to those determined by Wu et al (2014) using 41,819 SNPs across 367 inbred lines and finding values of 0.364 and 0.291, respectively. However, the values for average gene diversity and PIC in the present study are much smaller than those obtained in the three previous studies (Xie et al 2007;Yang et al 2010;Yu et al 2007), all of which found average gene diversity and PIC values of[0.500.…”
Section: Genetic Diversitysupporting
confidence: 79%
“…In the present study, the five subgroups Lan, LRC, PB, Reid, and SPT were defined in a manner largely consistent with the subgroups defined by previous studies (Wu et al 2014;Xie et al 2007;Yu et al 2007). Differences in the numbers of inferred subgroups can be attributed to the difference in the numbers and kinds of markers and inbred lines used in population structure studies Xie et al 2007;Yang et al 2010;Yu et al 2007).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations